Impact of Stopping Trastuzumab in Early Breast Cancer: A Population-Based Study in Ontario, Canada. (28th April 2020) - Rushton, Moira; Lima, Isac; Tuna, Meltem; Johnson, Chris; Ivars, Josee; Pritchard, Kathy; Hawken, Steven; Dent, Susan
Abstract: Background: Adjuvant trastuzumab for early-stage (I-III) HER2-positive breast cancer (BC) has led to statistically significant improvement in cancer outcomes but carries a risk of cardiotoxicity. Trastuzumab is discontinued early in many patients for asymptomatic changes in left ventricular ejection fraction. We evaluated the impact of early discontinuation of trastuzumab on cancer outcomes. Methods: We conducted a retrospective population-based cohort study of early BC patients treated with adjuvant trastuzumab in Ontario, Canada, 2007-2016. Four groups were analyzed: group A was full treatment, 17-18 cycles trastuzumab; group B was cardiac event (CE) within treatment period; group C was ≤16 cycles, no CEs, stopped within 30 days from last cardiac imaging; and group D was ≤16 cycles, no CEs, stopped more than 30 days from cardiac imaging. Primary outcome was disease-free survival (DFS); secondary outcomes were: overall survival, cancer-specific mortality, and cardiovascular mortality. Sensitivity analyses were performed 14 months after cycle 1 trastuzumab to control for early relapse. Results: A total of 5547 patients met the inclusion criteria: group A = 3921, group B = 309, group C = 362, and group D = 955. The 5-year DFS was 94.1% in group A, 80.1% in group B, 81.4% in group C, and 82.4% in group D. Using a Cox model, the hazard ratio for 5-year DFS was 3.15 (95% confidence interval [CI] = 2.13 to 4.65) for group B, 1.94 (95% CI = 1.30 to 2.89) for group C, and 1.92 (95% CI = 1.46 to 2.53) for group D. Overall, 26 patients (0.5%) died of cardiac causes. Conclusions: BC patients in Ontario who did not complete adjuvant trastuzumab had a statistically significantly higher risk of BC relapse and death and low incidence of cardiac death. These findings support 1 year of adjuvant trastuzumab in early-stage BC.